The Time Change of the Consumer Price Index Response to the Supply Chain Management in the Supply of Money in the Iraqi Economy - Othman hussein, Burhan (International Journal of Supply Chain Management, 2019)
The broadly acknowledged notion on inflation is that it is a money related event. Henceforth the decrease of expansion is to a great extent the domain of financial approach. This investigation is carried out with an objective to determine the direction and significance the relationship among money supply and inflation. Consumer price index is used as proxy of inflation while M2 is used to determine money supply in the country. We applied ARDL model to investigate long run relationship among the variables. The data used for this estimation is ranging from 1960 to 2017. Results of the study describe a unidirectional relationship from money supply to inflation. Therefore, a significant and positive long run relationship has established in Iraqi economy. Hence, monetarist point of view is prevailed in Iraqi economy. It is recommended that Iraqi government should tighten its monetary policy to control inflation within an acceptable range.